EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DENGAN STRATEGI PETA KONSEP PADA MATERI SEGIEMPAT DITINJAU DARI KEMAMPUAN SPASIAL PESERTA DIDIK - Yuwono, Muhammad Ridlo; Budiyono, Budiyono; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objective of this research was to know the effect of the learning models on the learning achievement of quadrangle viewed from the spatial ability of the students. The learning models compared were the cooperative learning model of the TGT type with concept mapping strategy, the cooperative learning model of the TGT type, and the direct learning model. This research used the quasi experimental method. Its population was all of the students in grade VII of State Junior Secondary Schools of Pati regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the research consisted of 325 students. They were grouped into three groups, namely: 109 in experimental group 1, 110 in experimental group 2, and 106 in control group. The instruments to gather the data were test of achievement on the learning topic of quadrangle, and test of spatial ability. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. The results of the research were as follows. (1) The cooperative learning model of the TGT type with concept mapping strategy results in a better learning achievement than the cooperative learning model of the TGT type and the direct learning model, but the cooperative learning model of the TGT type results in the same learning achievement as the direct learning model. (2) The students with the high spatial ability had the same learning achievement as those with the moderate spatial ability, but the students with the high spatial ability and those with the moderate spatial ability had a better learning achievement than those with the low spatial ability. (3) In each category of the spatial abilities, the cooperative learning model of the TGT type with concept mapping strategy results in a better learning achievement than the cooperative learning model of the TGT type and the direct learning model, but the cooperative learning model of the TGT type results in the same learning achievement as the direct learning model. (4) In each of the learning models, the students with the high spatial ability had the same learning achievement as those with the moderate spatial ability, but the students with the high spatial ability and those with the moderate spatial ability had a better learning achievement than those with the low spatial ability.Keywords: TGT, concept mapping, and spatial ability.